Efektivitas Pembelajaran Berbasis Masalah terhadap Kemampuan Berpikir Kritis dan Literasi Matematis pada Materi Barisan dan Deret Aritmatika kelas X SMK Telkom 1 Medan T.A 2025/2026. - gultom, eva meliana; Tambunan, Hardi; Simanjuntak, Ruth Mayasari (Universitas PGRI Semarang, 2026)
This quantitative study, employing a one-shot case study design, evaluates the effectiveness of problem-based learning (PBL) on students’ critical thinking skills and mathematical literacy in the topic of arithmetic sequences and series for 10th-grade students at SMK Telkom 1 Medan during the 2025/2026 academic year. The sample was randomly selected from two classes (X RPL 1 and X RPL 2) out of a total population of five classes. Data were collected through tests, questionnaires, and observations that had been validated for validity and reliability, then analyzed descriptively using frequency distribution tables and criteria for the achievement of learning objectives. The results showed that all indicators of effectiveness namely, the systematic nature of instruction, teacher communication, student responses, student activities, and the achievement of learning objectives were met. Thus, the PBM was deemed effective in improving critical thinking skills and mathematical literacy in the subject matter, with the level of effectiveness falling into the high category.